Atitudes das enfermeiras frente à morte dos pacientes em uma unidade de cuidados intensivos] [Actitudes de las enfermeras frente a la muerte de los pacientes en una unidad de cuidados intensivos (2023)
Introduction: In intensive care units (icu), contact with death is frequent for nurses who work there. In our country, this issue has been little studied. The objective of this study was to describe attitudes towards death in a group of nurses who work in a highly complex icu. Materials and methods: This descriptive study included 17 nursing professionals working in a highly complex icu. The revised profile of attitudes toward death was applied. Continuous variables were reported as average accompanied by standard deviation, given that they had a normal distribution according to the Shapiro-Wilk test and other graphic ones. Categorical variables were expressed as absolute or relative frequencies. Results: The overall average of the attitude towards death scale was 133.53 ± 21.50. The attitude with the highest average was the acceptance approach with 48.17 ± 12.64, followed by neutral acceptance with 28.94 ± 4.62, and fear of death with 23.0 ± 7.42. There is a moderate and direct correlation between the general average of the scale of attitudes toward death and years of work in the service, rho = 0.59, p = 0.016. Conclusions: Among the participants’ attitudes towards death, the one that prevailed most was acceptance approach. Additionally, it was established that there is a moderate and direct correlation between the general average of the scale of attitudes towards death and the years of work in the icu. © 2019, Universidad del Rosario. All rights reserved.